Reading Education in The Midst of Globalisation - Nadeak, Bernadetha; Wiryadinata, Halim (Universitas Negeri Padang, 2026)
The purpose of this study is to observe that the value of education in the era of globalisation has shifted from education to economic education. Education, which has a noble ideal of liberating humans from a life of shackles, has become economic education with a single goal: profitability in the era of globalisation. The narrative of globalisation promotes the connectedness and interdependence between individuals and ideas, but places education within a perspective of industrial education. This study employs a sociological approach to critically and logically explain this shift, drawing on access to books, journals, academic writings, and historical manuscripts. The results of this study suggest that globalization, driven by technological advancements, has transformed education into a commodity in the industrialization process. Ultimately, the conclusion of this study is the shift in educational values brought about by technological developments, which have elevated economic education as a key educational value in the era of globalisation.